The ligand influence in stereoselective carbene transfer reactions promoted by chiral metal porphyrin catalysts. Issue 40 (29th June 2016) - Intrieri, Daniela; Carminati, Daniela Maria; Gallo, Emma
Abstract : This Perspective illustrates the state-of-the-art of stereoselective carbene transfer reactions catalysed by chiral metal porphyrin complexes. A particular attention is focused on the active role of the porphyrin ligand to drive the carbene insertion into the target organic skeleton. Abstract : The use of diazo reagents of the general formula N2 C(R)(R 1 ) as carbene sources to create new C–C bonds is of broad scientific interest due to the intrinsic sustainability of this class of reagents. In the presence of a suitable catalyst, diazo reagents react with several organic substrates with excellent stereo-control and form N2 as the only by-product. In the present report the catalytic efficiency of metal porphyrins in promoting carbene transfer reactions is reviewed with emphasis on the active role of the porphyrin skeleton in stereoselectively driving the carbene moiety to the target substrate. The catalytic performances of different metal porphyrins are discussed and have been related to the structural features of the ligand with the final aim of rationalizing the strict correlation between the three-dimensional structure of the porphyrin ligand and the stereoselectivity of carbene transfer reactions.